Active realization of fractional order Butterworth lowpass filter using DVCC - Shalabh Kumar Mishra; Maneesha Gupta; Dharmendra Kumar Upadhyay (Journal of King Saud University: Engineering Sciences, 2020)
This paper presents an active realization of fraction order Butterworth lowpass filter using a differential voltage current conveyor (DVCC) and two fractance devices (FDs). Initially, the DVCC based fractional order system transfer function is developed. Then, the transfer function of the developed system is equated with the standard fractional order Butterworth equation. By equating this, the generalized condition is obtained for which the developed system behaves like a fractional order Butterworth filter. Further, the effect of current and voltage tracking errors of DVCC, on the system response is investigated using Monte Carlo analysis. Stability of the proposed fractional order Butterworth filter is investigated by pole-zero analysis in complex W-plane. Moreover, the dependency of filter cutoff frequency, on various circuit parameters are investigated using 3D plots. Finally to validate the theoretical results, proposed fractional order Butterworth filter is simulated using R-C ladder network based fractional order capacitor, in PSpice environment using 0.5 μm MIETEC CMOS technology. Keywords: Fractance device, Fractional order filter, Ladder network, W-Plane